1994
DOI: 10.1002/ange.19941060923
|View full text |Cite
|
Sign up to set email alerts
|

Synthese ungesättigter Aminosäuren durch [3,3]‐sigmatrope Umlagerung chelatverbrückter Glycinesterenolate

Abstract: ZUSCHRIFTENviolett. Nach langsanieni Erwiirmen wird die Reaktionslosung kurzzeitig bei -78°C geriihrt. Feinverteiltes Lic'I lHl3t man iiber Nacht bei -92 C absitzen. die klare Losung wird mit einem diinnen Teflonschlauch in eine abschmelzbare Glasampulle gedruckt. Ini Hochvnkuum hei -8.5 'C wird auf l/5 des ursprunglichen Volumens eingeengt. danach liilll durch Kiihlen auf -1 15' C ein violettes Kristallpulver aus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 53 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…Moreover, the Irelend-Claisen rearrangement of a-substituted acetic acid esters of the mentioned fluorinated allylic alcohols such as achloroacetic esters or propionic esters, led to the corresponding 2-substituted 4-fluoroalk-4-enoic acids in moderate yields [9]. The reaction was shown to work also with N-protected glycine esters to give 2-amino-4-fluoroalk-4-enoic acids in excellent yields in a modified Kazmaier variation [10] of the IrelandClaisen rearrangement [11]. Furthermore, we have shown that N-benzoyl protected fluorinated allylic esters of alanine or phenylglycine gave the corresponding N-benzoyl 2-amino-4-fluoro-2-methyl(or phenyl)-alk-4-enoic acids in almost quantitative yield following the mechanism of the Steglich variant [12] of the Ireland-Claisen rearrangement [13].…”
Section: Introductionmentioning
confidence: 96%
“…Moreover, the Irelend-Claisen rearrangement of a-substituted acetic acid esters of the mentioned fluorinated allylic alcohols such as achloroacetic esters or propionic esters, led to the corresponding 2-substituted 4-fluoroalk-4-enoic acids in moderate yields [9]. The reaction was shown to work also with N-protected glycine esters to give 2-amino-4-fluoroalk-4-enoic acids in excellent yields in a modified Kazmaier variation [10] of the IrelandClaisen rearrangement [11]. Furthermore, we have shown that N-benzoyl protected fluorinated allylic esters of alanine or phenylglycine gave the corresponding N-benzoyl 2-amino-4-fluoro-2-methyl(or phenyl)-alk-4-enoic acids in almost quantitative yield following the mechanism of the Steglich variant [12] of the Ireland-Claisen rearrangement [13].…”
Section: Introductionmentioning
confidence: 96%
“…Attempts to achieve a Claisen rearrangement on 12 under Kazmaiers, [12] Irelands, [13] or Johnsons [14] conditions failed.…”
mentioning
confidence: 93%
“…[23] These enolates are excellent nucleophiles for transition-metal-catalyzed allylic alkylations, [24] giving rise to γ,δunsaturated amino acids. The same structural motif can be obtained through a chelate-enolate Claisen rearrangement, [25] an approach well suited for highly functionalized amino acids [26] and peptides. [27] Here we wish to report on an application of this protocol for the synthesis of Aoe and chlamydocin.…”
Section: Introductionmentioning
confidence: 99%